Padrões de orçamento familiar: uma análise mercadológica - Silva, Hermes Moretti Ribeiro da (2009)
It is becoming more and more recognizable that different family budget categories dispute the limited resources of a family. This suggests a broader and more systemic competition view, once consumer spending on a determined sector may be better understood if related to other sectors. Thus, it is reasonable to concentrate studies in the manifestation of the buyer behavior, expressed by the family budget, whereas priority/vital-based decisions are established according to how the consumers distribute their resources in great categories of expenses (food, housing, transportation, clothing, leisure etc). In this context, the main objective of this research is outlined, which is to investigate the phenomenon of the allocation of such expenses that compose the family budget, identifying patterns, market segmentation and its implication in Marketing. The theoretical referential is divided in three great parts: market segmentation, family budget, and the economic and socio-demographic factors that relate to the family budget. Maslow’s Classic Hierarchy of Needs is approached, along with themes from economics literature such as Engel’s Law and Income-elasticity of Demand. Using data collected from a sample of families in the State of São Paulo and applying Cluster Analysis, this study aims to bring a perspective that is more influenced by the paradigms of the market knowledge by identifying and characterizing market segments with distinctive patterns of family budget. A taxonomy based on six patterns was formed, which are: survival, ill, economic, domestic, well being and automobile. Each pattern analysis enhances economic and socio-demographic similarities and differences that demand the attention of researchers and marketing strategists concerning the generalization problems, which may result in mistakes in market segmentation strategies. Discussions concerning the Maslow’s Theory and Engel’s law are made. Furthermore, taxonomy of family expenses classified by the income-elasticity among the six identified family budget patterns is proposed. This taxonomy helps clarify changes in consuming behavior according to the impact in income alterations in the composition of the family budget. Finally, results reinforce the thesis that patterns in family expenses allocation present an innovative and useful dimension for studies in market segmentation.